Ultrasound characterization of the abdominal organs of the margay (Leopardus wiedii) in captivity - Grandez R., Ricardo (2019)
The margay (Leopardus wiedii) has been considered in Appendix I of CITES since 1990, and in the IUCN red list. In Peru it is classified as a "species with insufficient data" within the categorization of Endangered Species of Wild Fauna of the Ministry of Agriculture and Irrigation (MINAGRI). The purpose of this study was to describe the morphology and topography of the abdominal organs of the margay in captivity. The work included the six specimens, five females and one male, raised in the Zoological Park of Huachipa, Lima, Peru. The animals were anesthetized to perform the ultrasound technique. A Pie Medical Falco, with a multifrequential transducer of 5-7.5 MHz was used. The topography, shape, ecotexture, margins and architecture of the liver, gallbladder, kidneys, stomach, spleen, urinary bladder and testicles were evaluated. It was concluded that the ultrasonographic characteristics found in the spleen, bladder, liver, stomach, gallbladder and testicles were similar in terms of echogenicity, margins and topography to that of some domestic carnivores such as the cat and the dog; the shape of the kidneys was elongate, recalling more the shape of domestic dogs, while the spleen and stomach presented slightly more elongated forms than those described in the domestic cat.